Peliosanthes lihengiae (Asparagaceae: Convallarioideae), a new species from Yunnan, Southwestern China - Han, Hui; Gong, Qiang Bang; Yv, Ze Bin; Wang, Wen; Yan, Mao Lin; Ye, Xi Yang; Yuan, Juan Juan; Feng, Hui Zhe (Phytotaxa, 2026)
During a botanical expedition on the eastern slopes of the Gaoligong Mountains in western Yunnan, China, a distinctive new species was discovered and is described here as Peliosanthes lihengiae H.Z.Feng & Q.B.Gong, sp. nov. Morphological analysis confirms that this taxon is readily distinguished from all known congeners by its unique combination of characters: the well-developed aerial stems, a nearly sessile inflorescence, deep purple flowers, and a corona slightly convex, obscurely circular in outline. The new species is most closely allied to P. sessilis, but key diagnostic differences are found in its glabrous leaf veins, longer inflorescence (–6 cm), purple (vs. yellowish-green) flowers, and distinct corona morphology.